Hubungan antara Pola Interaksi Orang Tua-Anak dengan Perilaku Agresif pada Remaja di SMP Negeri 1 Kuta Utara - Ni Kadek Sonia Pratiwi; Komang Trisna Sumadewi; I Gusti Rai Tirta (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Aggressive behavior can be interpreted as an act intended to injure or hurt another person, both physically and psychologically, resulting in harm or harm to others. There are various forms of aggressive behavior that can be observed in our daily life, including berating, mocking, cursing, rioting, and all kinds of behavior that lead to acts of violence. This study aims to explain the relationship between parent-child interaction patterns with aggressive behavior in adolescents at SMP Negeri 1 Kuta Utara. The design used was analytic and a cross sectional approach. This research was done at SMP Negeri 1 Kuta Utara. The samples was 100 people that selected by the proportional stratified random sampling method. The data was obtained from filling out the PACHIQ-R questionnaire and the aggressiveness questionnaire by the respondents, then the data were analyzed using univariate analysis and bivariate analysis using the Pearson Correlation Test. The results of the study with the Pearson Correlation Test found that the correlation coefficient between parent-child interaction patterns with adolescent aggressive behavior was -0.216 with a significance of 0.031 where the value was smaller than the significant level <0.05, the strength of the relationship was weak with the correlation value. 0.216. The direction of the correlation is negative (-) which means that the better the parent-child interaction pattern, the lower the aggressive behavior of adolescents.